CASE BASED CURRICULUM IN ADMINISTRATION AND LEADERSHIP COURSE - Kapti, Suzan Beyza; Beyaztas, Dilek Ilhan; Kapti, Alican; Senemoglu, Nuray (European Scientific Journal, ESJ, 2015)
Law enforcement training institutions carry out important responsibility by training police officers to serve community. As usual in all training institution, the success of this institution is based on designing of efficient and effective curriculum for the students. For this purpose, a casebased curriculum was developed for the Administration and Leadership course at the Faculty of Security Sciences (FSS) at Turkish National Police Academy (TNPA) and this research evaluates its effectiveness. As data collection tools, a summative test was developed in order to specify differences between students’ average achievement scores of pre-test and post-test. In addition, a semi-structured interview instrument regarding to the Administration and Leadership course curriculum was developed to specify the opinions of students and trainer. A statistical significant difference was captured between students’ pre and post-tests scores. In addition the students and trainers involved in the Administration and Leadership course curriculum provided positive feedbacks about the program.